Power and Equity in the Academy: Change from Within - Hisama, Ellie M. (Current Musicology, 2018)
As an undergraduate music major interested in graduate study in music theory, I asked Joseph Straus, with whom I was taking an independent study in music theory and feminism, if he knew of any published work in feminist music theory. The only relevant writing he could think of was Susan McClary’s “Pitches, Expression, Ideology,” from the little-known journal Enclitic (1983). After reading this article (which I still reference when teaching Schubert Lieder), I corresponded with McClary, and we set up a meeting during her visit to New York to speak at the Brecht Forum/ New York Marxist School. We quickly bonded over the fact that we both grew up in the same small town in Illinois—Carbondale—and that in graduate school we both tried desperately to expunge all traces of our distinctive southern Illinois twang. As a first-year music theory graduate student at Harvard eager to bring feminist criticism to my newly chosen subfield, I established a study group for those interested in learning more about what then was a brand-new area of research. The Group for Gender Studies in Music (GGSM) met once a month to discuss the few publications then available in feminist music studies, analyze music by women composers, produce a concert of music by women composers in honor of Women’s History Month, and plan a colloquium series. We found a sympathetic adviser in David Lewin, the senior music theorist on the faculty, and I secured funding from Radcliffe College and several other sources to pay for honoraria and travel for our four invited speakers. Lewin generously wrote a check as seed money to support our group when our request for department funding for our activities was turned down. When I met with the department chair about possible support for GGSM, I was asked to supply a list of names of those who attended our meetings, ostensibly to establish the level of student interest in the group. Our group was more controversial than I had anticipated and I wondered whether there would be negative consequences for anyone involved. (I did not comply with the request for names.) Without support from the department, we could not internally process the donations we received, and had to open an account at a local bank. Meetings of the Group for Gender Studies in Music were very well attended by curious graduate students in music theory, musicology, and ethnomusicology. Word of our colloquium series, advertised in hard-copy posters I prepared with my dot-matrix printer in the days before Facebook, Twitter, and e-mail somehow reached Professor Judith Tick at Northeastern University and Dr. Hugh Morgan Hill, also known as Brother Blue. Dr. Hill was a playwright and storyteller based in Cambridge who had earned a doctorate in storytelling from Union Graduate School (Grimes 2009). He attended McClary’s GGSM colloquium on Laurie Anderson, work she developed into a chapter in Feminine Endings (1991), and he took McClary aside to comment on the significance of her speaking about Anderson within the staid wood-paneled seminar room in Harvard’s historic Paine Hall.[1] While many of my fellow graduate students welcomed the opportunity to engage with this new area of study, most of the faculty did not. Apart from Lewin, no faculty member ever attended a GGSM meeting and few attended our public colloquia, despite the prominence of the speakers we scheduled, including musicologists McClary and Paula Higgins, music theorist Joseph Straus, and composer and theorist Pozzi Escot. Although I had made it clear in my applications to PhD programs that I was determined to bring feminism to music theory, my attempts to initiate thinking at Harvard about gender, feminism, sexuality, race, and music got serious pushback. One graduate student relayed that his adviser mentioned to him that I should not be organizing numerous events he didn’t have time for, because when he didn’t attend, everyone would wonder why he wasn’t there. The department, and the field, were not ready in 1990 for such research directions.[2] During her visit to GGSM, McClary pointedly told me, “it doesn’t have to be this way” (i.e., being miserable in graduate school). While taking a leave of absence from Harvard, I spent a glorious year at the University of Minnesota studying with McClary in the School of Music and with Richard Leppert and Lisette Josephides in the interdisciplinary PhD program in Comparative Studies in Discourse and Society. Working with these cutting-edge scholars and superb teachers proved to be an antidote to my disastrous first year of graduate school. At Minnesota, McClary was a magnet for a cohort of smart, curious, imaginative, and fun graduate students who were all interested in possibilities for new scholarship that brought critical theory, including feminist theory, to the study of all sorts of music, from Beethoven to Madonna, Monteverdi to Prince. McClary’s professional home is often assumed to be musicology, but many of us who have PhDs in music theory consider her to be a theorist. She has always insisted on thinking about how structure and processes are an integral part of the critical questions she raises about representation, narrative, tropes, and musical meaning, viewed through various lenses including gender and sexuality. I took two seminars with her—one on Monteverdi’s madrigals and another on music and postmodernism. The paper I wrote for the latter seminar turned into probably the most widely read piece I’ve published, my article on representations of East Asian women in music by John Mellencamp, David Bowie, and John Zorn (Hisama 1993). After Bowie’s death in 2016, I received calls from journalists who located that article from 1993 and wanted me to comment on Bowie and racism (Tam 2016 and Tandon 2016). Notes For a history of Paine Hall, see Brinkmann and Bannatyne (2010). As of Fall 2018, Harvard has not offered a seminar in gender studies and music. Personal communication with Anne Shreffler, San Antonio, TX, November 2018.